Accentuating illocutionary forces: emoticons as speech act realization strategies in a multicultural online communication environment - Azianura Hani Shaari, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The global acceptance of emoticons has acknowledged the development of digital symbols in a communication setting when language alone can become a barrier in expressing certain intentions and feelings. This paper discusses how emoticons help indicate the illocutionary forces in texts and serve as part of various conversation strategies in the online communication environment. To achieve the research objective, a documentation of naturally occurring conversations on Facebook was made over a 12-month period to compile daily updates and conversations posted by youngsters in Malaysia. 120 online users were identified using a purposive sampling technique. A corpus of 324 362 words was established and processed. This whole set of naturally occurring conversation was then analysed based on Searle’s (1976) five categorisations of illocutionary acts using Content Analysis and Wordsmith Tools 5.0. The findings demonstrate some emoticons that accentuated illocutionary forces of speech acts in the online communication environment. Discussion of the findings also explores the purposes and functions of emoticons in Malaysian digital communication platform and the way users of a multicultural society employ emotion-symbols to achieve social cohesion and embrace cultural diversity.